The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1677/erc-07-0144
|View full text |Cite
|
Sign up to set email alerts
|

Anti-estrogenic actions of histone deacetylase inhibitors in MCF-7 breast cancer cells

Abstract: Anti-estrogens are the current endocrine therapy of choice in the treatment of estrogen receptor (ER)-positive breast cancers. Histone deacetylase inhibitors (HDACi) also constitute a promising treatment for therapy, and combination of anti-estrogens with HDACi may improve efficacy while reducing side effects. We have examined the effect of the HDACi sodium butyrate and suberoylanilide hydroxamic acid (SAHA), alone and in combination with 17b-estradiol (E 2 ) and the pure anti-estrogen ICI 182.780 (ICI) in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 41 publications
(54 reference statements)
5
32
1
Order By: Relevance
“…An interesting feature of rye bran is the production of SCFAs, especially butyrate, in the gut [39,57]. Butyrate is a histone deacetylase inhibitor that inhibits E 2 -induced expression of estrogen target genes and proliferation of MCF-7 cells [58,59]. Perhaps butyrate production explains some of the estrogen antagonism in the rye-fed mice in our study.…”
Section: Effects Of the Diets On E 2 -Induced Eventsmentioning
confidence: 63%
“…An interesting feature of rye bran is the production of SCFAs, especially butyrate, in the gut [39,57]. Butyrate is a histone deacetylase inhibitor that inhibits E 2 -induced expression of estrogen target genes and proliferation of MCF-7 cells [58,59]. Perhaps butyrate production explains some of the estrogen antagonism in the rye-fed mice in our study.…”
Section: Effects Of the Diets On E 2 -Induced Eventsmentioning
confidence: 63%
“…However, it should be noted that this modification cannot be univocally linked to transcriptional activation, because ER antagonists also cause Ser-118-ERa phosphorylation (Lipfert et al, 2006). In fact, we have previously shown that ICI is at least as strong as E2 to induce a sustained increase of Ser-118-ERa phosphorylation in MCF-7 cells (De los Santos et al, 2007), and in this work we observe that ER antagonists cooperate with PRL to increase P-Ser-118-ERa levels. In addition to ERa phosphorylation, the activation of ERK1/2 and AKT by PRL may also lead to phosphorylation of receptor co-regulators (co-activators and co-repressors).…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture and transfection T47D and MCF-7 cells were grown in Dulbecco's modified Eagle's medium supplemented with 10% fetal calf serum, 2 mM glutamine, 100 IU/ml penicillin and 100 mg/ml streptomycin, and 72 h before transfection were shifted to serum-free medium lacking phenol red. Cells were transiently transfected with 5 mg of a luciferase reporter plasmid that contains three copies of a consensus ERE by incubation with a mixture of cationic liposomes (1.5 ml/mg DNA) for 6 h (De los Santos et al, 2007). Cells were then treated with 100 nM PRL, ICI or E2 for the indicated times, and luciferase activity was determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations